Effect of mRNA Delivery Modality and Formulation on Cutaneous mRNA Distribution and Downstream eGFP Expression - Aditya R. Darade; Maria Lapteva; Thomas Hoffmann; Markus Mandler; Achim Schneeberger; Yogeshvar N. Kalia (MDPI AG, 2022)
In vitro transcribed messenger ribonucleic acid (mRNA) constitutes an emerging therapeutic class with several clinical applications. This study presents a systematic comparison of different technologies-intradermal injection, microneedle injection, jet injection, and fractional laser ablation-for the topical cutaneous delivery of mRNA. Delivery of Cy5 labeled mRNA and non-labeled enhanced green fluorescent protein (eGFP) expressing mRNA was investigated in a viable ex vivo porcine skin model and monitored for 48 h. Forty 10 µm-thick horizontal sections were prepared from each skin sample and Cy5 labeled mRNA or eGFP expression visualized as a function of depth by confocal laser scanning microscopy and immunohistochemistry. A pixel-based method was used to create a semi-quantitative biodistribution profile. Different spatial distributions of Cy5 labeled mRNA and eGFP expression were observed, depending on the delivery modality; localization of eGFP expression pointed to the cells responsible. Delivery efficiencies and knowledge of delivery sites can facilitate development of efficient, targeted mRNA-based therapeutics.